"Corporate" and "Community" Takāful - Arbi, Lukman Hanif (Journal of the Indonesian Mathematical Society, 2025)
In this paper, we compare different characterizations of the tak¯aful organization. We propose two different characterizations with one being based on conventional firm theory from microeconomics (“corporate” takāful) and another being based on the mutual/cooperative insurance literature (“community” takāful). We find that both characterizations imply different strategies due to different objectives and operational conditions. We also find that if participants in a community takāful organization are altruistic, those overseeing the organization must make sure that participants do not spend more than they have when paying for claims made by the community.